Benefiting from International Experiences to Develop Higher Technical Education in Libya (Journal of human and social sciences, 2022)
This study addresses the challenges facing technical education in Libya, particularly the weak quality of its outcomes, its disconnection from labor market needs, and the negative social perception surrounding it. The paper reviews selected successful Arab and international experiences in developing technical education, with the aim of drawing lessons for improving the quality of higher technical education in Libya. It emphasizes the necessity of a comprehensive reform process that includes curriculum development aligned with labor market requirements, and stronger cooperation between educational institutions and the economic sector. Such reforms are essential to prepare qualified human resources capable of supporting national economic growth and addressing rising unemployment.
Keywords: Technical Education; Labor Market; Educational Reform; Economic Development; Unemployment